(untitled) (Pedagogical Horizons, 2024)
Approximately 17% of apprentices in Austria do not complete their vocational training. Dropping out of education is associated with numerous personal disadvantages for those affected and high costs for society. Efforts should be made to counteract this. An indication of dropping out of education can be absenteeism from school. Accurate records of absences and subsequent educational diagnostics in schools are recommended. This way, teachers can become aware of at-risk students and implement appropriate prevention and intervention measures. Existing literature on school absenteeism often focuses on full-time schools. In dual education, the vocational school is only one of two learning venues. Students there are either in part-time or block teaching, primarily in what is known as course-based schooling in Austria. In the latter case, students only attend school once a year for a block of 9-10 weeks. The question arises as to how vocational school teachers monitor absences under these conditions. This work provides insights into a survey as the first phase of an action research project on how absenteeism is currently collected and analyzed at vocational schools in Upper Austria.